Women's Leadership Management Model in Islamic Higher Education Institution - Fuadi, Athok; Mustaqim, Azmi; Bueraheng, Ibroheng; Efendi, Arief (IAIN Ponorogo, 2024)
This study examines the management model of women’s leadership in Islamic higher education institution. Amidst the unpopularity of women leaders leading public Islamic religious universities, IAIN Ponorogo has been led by women for over a decade (2010-2023). This research employed a qualitative methodology involving some women leaders at IAIN Ponorogo, mainly the current rector and two heads of study programs. This research is limited to examining the last period of current women's leadership. The results of this study reveal that leaders at IAIN Ponorogo have standards for building the quality of higher education. The women's leadership management model tends to be feminist-transformational, which explores how women leaders contribute to the main elements of management: input, process, and output. The role of leaders in the main aspects of management is to ensure the availability of input indicators, encourage implementation, assist implementation, be actively involved in process indicators, and produce a feminist-transformational leadership model in output indicators. The behavioral framework that shows feminist-transformational is a charismatic leader who can stimulate intellectually, have individual attention, and be an inspiration and motivation.